The DIVING3D Project: Analysis of the nuclear region of Early-type Galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Ricci, T. V.; Steiner, J. E.; Menezes, R. B.
Abstract: In this work, we present preliminary results regarding the nuclear emission lines of a statistically complete sample of 56 early-type galaxies that are part of the Deep Integral Field Spectroscopy View of Nuclei of Galaxies (DIVING 3 D ) Project. All early type galaxies (ETGs) were observed with the Gemini Multi-Object Spectrograph Integral Field Unit (GMOS-IFU) installed on the Gemini South Telescope. We detected emission lines in 93% of the sample, mostly low-ionization nuclear emission-line region galaxies (LINERs). We did not find Transition Objects nor H II regions in the sample. Type 1 objects are seen in ∼23% of the galaxies.